P67 Temporal trends in heart failure incidence among patients with COPD and all-cause mortality of patients with comorbid COPD and heart failure in UK primary care, 2006–2016. (December 2018) - Axson, EL; Sundaram, V; Gayle, A; Gulea, C; Bloom, CI; Zakeri, R; Bottle, A; Cowie, MR; Quint, JK
Abstract : Introduction and objectives: Having comorbid chronic obstructive pulmonary disease (COPD) and heart failure (HF) (COPD-HF) may significantly impact a patient's morbidity and mortality, though contemporary data are lacking. This study investigated HF incidence in a COPD population in UK primary care from 2006–2016. Methods: Using UK primary care electronic healthcare record data from the Clinical Practice Research Datalink, we identified patients with COPD-HF between 2006 and 2016. We calculated age and sex standardised (European Standard Population 2013) annual incidence of HF, first instance of HF clinical code, within the COPD population from 2006–2016. Using a population with prevalent COPD-HF and linked mortality data from the Office of National Statistics, we calculated the annual age and sex standardised mortality rate of patients with COPD-HF and the age and sex standardised mortality rate ratio (ASMRR) compared with patients with COPD alone. Results: We identified 1 94 783 patients with COPD, of whom 11.0% had comorbid HF (n=21, 489). Standardised HF incidence was steady from 2008 to 2016 (0.40 to 0.41 per 100 person-years; figure 1). Standardised mortality of patients with COPD-HF declined (9.07 to 7.01 per 100 population, 2006–2016; figure 1). The 10 year ASMRR versus patients with COPD alone was 3.40 (95% CI 3.36 to 3.44). Conclusions: HF incidence in COPD patients has remained steady over the past 10 years; in contrast, HF incidence has declined in the general UK population. 1 All-cause mortality in COPD-HF patients has decreased over time, suggesting better HF management or earlier diagnosis in people with COPD. Reference: Conrad N et al . 2018. doi:10.1016/S0140–6736(17)32520–5